Functional disorders of musculoskeletal system and risk factors of related injuries in young track and field athletes - A. Matishev; S. Loktev; G. Makarova (Спортивная медицина: наука и практика, 2020)
Objective: to identify the most frequent internal risk factors for chronic and acute injuries of musculoskeletal system in young track and field athletes. Materials and methods: 33 track and field athletes (runners and long jumpers) aged from 11 to 17 years old were examined. Following parameters were assessed: ankle extension, flexion, pronation and supination; tonus of hamstring and flexibility of its tendons; tonus of iliopsoas muscle and rectus femoris; data from digital photometric plantography. Results: the following frequency of functional disorders of musculoskeletal system of the examined athletes was found: impairments of ankle extension degree, enhanced foot supination, enhanced foot pronation, forefoot valgus, great tonus of hamstring, low proprioceptive sensibility. The identified functional disorders of musculoskeletal system (and lower limbs in particular) may result in its subsequent chronic and acute injuries. Conclusions: biomechanical basis for impairments of musculoskeletal system in athletes (including runners for different distances) is attributable to their sports activities in childhood and adolescence. Scope of measures preventing chronic overexertion and acute injuries of musculoskeletal system should be developed from the early start in particular sports and according to internal and external risk factors.